The Qawaid Nahwu’s Learning Contribution to Reading Skills (American Journal of Education and Technology, 2023)
This study aimed to determine and analyze the contribution of qawa’id nahwu learning in improving reading skills in Arabic language program students. This study uses a qualitative method with the data source selected by purposive sampling. The types of data in this study were primary data and secondary data. In contrast, the data collection techniques in this study used observation, interviews and subject interpretation of the questions posed by the researcher. The data analysis technique uses data reduction stages, data presentation, drawing conclusions, and verification. The results showed that the qawa’id nahwu method implemented for students proved to be more effective in improving reading abilities and skills in learning Arabic when compared to conventional methods. Other findings indicate that there are still inhibiting factors in implementing the qawa’id nahwu method, including environmental factors and internal factors from the individual students themselves. Therefore, efforts to overcome the obstacles of learning qawa’id nahwu can pay attention to five external factors: the competence of Arabic language lecturers, the learning methods used, the Arabic language material being taught, adequate infrastructure facilities, and a supportive environment.